Evaluation of a novel virtual reality immersive clinical experience to enhance medical education curriculum - Lai, Michael; Taheri, Kamyar; Aziz, Rem; Milaire, Paul; Rothman, Zachary; Shi, Kevin; Nazerali-Maitland, Alasdair (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Implication StatementMedical students often find the transition to clerkship challenging and stressful. The use of virtual reality (VR) technologies such as screen-based learning, 360-video and immersive VR using head-mount-devices is becoming more utilized in medical education. Immersive technologies in particular have been shown to lead to greater enthusiasm and provide higher knowledge gain for students compared to screen-based VR. The University of British Columbia Faculty of Medicine has developed a novel immersive patient experience using VR to enhance the clinical skills program and evaluate student perception regarding its formal integration into curricula. Students reported positive feedback on the experience, and interest in more immersive learning opportunities in future sessions. VR technology has the potential to enhance medical education and provide a safe immersive learning environment to build clinical acumen.